Honeycomb‐Structured 3D Concave Photovoltaic Modules Supported by 3D Mechanical Metamaterials for Enhanced Light Recapture. Issue 2 (11th November 2022) - Yun, Min Ju; Sim, Yeon Hyang; Lee, Dong Yoon; Cha, Seung I.
Abstract: For a policy of 100% renewable energy, most renewable‐energy research is aimed at decarbonization; particular emphasis is being placed on increasing the portion of electricity generated by photovoltaics (PVs). As the application fields of PVs broadens from PV power plants and rooftop to various urban environments, achieving high energy yields requires expansion beyond current PV module structures. To satisfy these demands, honeycomb‐structured PV modules with incorporated mechanical metamaterials are proposed, to overcome the aforementioned problems associated with the limited mechanical properties of PVs, and to advance the development of 3D PV modules with enhanced energy yield. The honeycomb structures provide 28% greater power compared with flat cells by utilizing extra reflected or scattered light inside a 3D tetrahedron structure. For mechanical robustness, the 3D concave tetrahedron units are supported by a 3D‐structured mechanical metamaterial that exhibits a negative Poisson's ratio and is arranged in a 3D pattern. Abstract : Honeycomb‐structured PV modules with incorporated mechanical metamaterials are proposed to overcome the aforementioned problems associated with the limited mechanical properties of photovoltaics, and to advance the development of 3D PV modules with enhanced energy yield. The honeycomb structures provide 28% greater power compared with flat cells by utilizing extra reflected or scattered light inside a 3D tetrahedron structure.